A configuração didática das práticas pedagógicas de professores/as da EJA em combate à LGBTfobia - Paiva, Camila de Lourdes Cavalcanti (2021)
The purpose of this dissertation consists to outline the didactic configuration of the pedagogical practices of EJA teachers in the fight against LGBTphobia. This research is justified by the low quantity of academic studies that correlate pedagogical practices, didactics, LGBTphobia and EJA. For that, a qualitative approach research was used, whose data generation took place through semi-structured interviews, with five teachers, who identified themselves as teachers whose practices were characterized as combating LGBTphobia. These teachers were selected by using the snow ball sampling technique. As a method of data analysis, in this work, the Critical Discourse Analysis (CDA) was used, based on studies by Fairclough (2012). In the data analysis, the teachers' speeches about their and the school role integrate a larger speech, which is justified in the maintenance of a traditional education, which sees the student as a deposit, which will receive the knowledge possessed by the teacher, and also constitutes the heteronormative idea that issues related to fighting LGBTphobia are summarized in working with sexually transmitted infections (STI's), such as HIV disease, or differences within a binary logic of male and female, which limits the thematic works on fighting LGBTphobia in science classes. We emphasize that EJA is a modality with a diversity of age, which covers young people, adults and seniors, and that matters considered intimate or prohibited can and should be dealt with, aiming to spread knowledge that will be useful to them in their lives within and out of school. Among the research findings, it is highlighted in the discursive practices that LGBTphobia constitutes a threat, that, sometimes, it is not identified by the teacher and, in some situations, it is practiced not only by students among themselves, but also by the teacher towards them. The fear of reprisal and the inefficient initial and continuing education are presented as difficulties in introducing the thematic into the pedagogical practices of teachers. The didactic configuration highlighted in the discursive practices of the research subjects is evidenced in the pedagogical practices that aim to bring knowledge to students, fight discrimination and prejudice, build a citizen awareness of respect and denaturalize the idea that there are only the genders and sexual orientations within the heteronormative logic. The need for new studies on pedagogical practices to combat LGBTphobia is highlighted, pointing out, as future possible investigative problems, those that observe how these pedagogical practices are worked on in teacher training courses, that give visibility to these pedagogical practices, in order to contribute to build an education based on dialogue, respect for diversity and empathy for others.